Differential maturation of rhythmic clock gene expression during early development in medaka (Oryzias latipes). (May 2014) - Cuesta, Ines H.; Lahiri, Kajori; Lopez-Olmeda, Jose Fernando; Loosli, Felix; Foulkes, Nicholas S.; Vallone, Daniela
Abstract : One key challenge for the field of chronobiology is to identify how circadian clock function emerges during early embryonic development. Teleosts such as the zebrafish are ideal models for studying circadian clock ontogeny since the entire process of development occurs ex utero in an optically transparent chorion. Medaka ( Oryzias latipes ) represents another powerful fish model for exploring early clock function with, like the zebrafish, many tools available for detailed genetic analysis. However, to date there have been no reports documenting circadian clock gene expression during medaka development. Here we have characterized the expression of key clock genes in various developmental stages and in adult tissues of medaka. As previously reported for other fish, light dark cycles are required for the emergence of clock gene expression rhythms in this species. While rhythmic expression of per and cry genes is detected very early during development and seems to be light driven, rhythmic clock and bmal expression appears much later around hatching time. Furthermore, the maturation of clock function seems to correlate with the appearance of rhythmic expression of these positive elements of the clock feedback loop. By accelerating development through elevated temperatures or by artificially removing the chorion, we show an earlier onset of rhythmicity in clock and bmal expression. Thus, differential maturation of key elements of the medaka clock mechanism depends on the developmental stage and the presence of the chorion.